Observation and Application of Digital Marketing in The Home Industry Benjeng District - Sumakul, Vione Deisi Oktavina (Kontribusia : Research Dissemination for Community Development, 2024)
Kedungrukem Village is one of the villages located in Benjeng District, Gresik Regency which consists of the hamlets of Kedungrukem, Kedung glugu, Ngablak, Bulak Ploso. By geographical, Village Kedungrukem is at in region Subdistrict Benjeng, Regency Gresik with a position bordered by Ploso Village to the west, Delik Sumber Village to the next south, Munggugianti Village to the east. Some of the professions of the people of Kedungrukem village big Work as farmers, traders, producer opaque, producer cage chicken And stab satay. We can know that Kedungrukem village has enormous potential because own a number of product superior that is Opaque Pinch. With implemented it digitalization marketing at one of the Opak Pin SMEs in Kedungrukem village, making Opak pinch a wider market share. Marketing is not only entrusted to shops or direct to consumer, However Can in a way on line through social media And market place.